AN ANALYSIS OF CONTROL IN SCIENTIFIC PUBLICATIONS IN PORTUGUESE AND IMPLICATIONS FOR THE FORMATION OF THE EXECUTIVE SECRETARIAT (REMUNOM, 2025)
This study aimed to analyze the control concepts present in scientific publications published between 2019 and 2024 in Portuguese so that their implications for the professional training of executive secretaries could be identified. The study's framework consisted of the management process theory, specifically the control process, its fourth and final stage so that the state-of-the-art knowledge produced and published in Portuguese could be understood. The conceptual bibliographic method was used, which consists of formulating research questions and their respective response patterns, followed by data collection in scientific databases, which were then organized in the form of frequency tables and diagrams representing the logical scheme of the attributes of the control process, ending with the writing of the responses sought for submission to the scientific community for consideration. The data collected were conceptual definitions contained in these publications from 2019 to 2024 in 10 studies that underwent semantic analyses to generate the findings. The results indicated the existence of four approaches to control (action, function, support, and process), six attributes that characterize the control process and five implications for the training of executive secretarial professionals: 1)leadership in the execution of organizational strategies, 2) the ability to influence people to lead them, 3) mastery over control devices and applications, 4) focus on the performance predicted in the plans and 5) the establishment of a safety environment to achieve organizational objectives. The study's findings contribute to improving the training of executive secretarial professionals by positioning them as support for managers in achieving organizational objectives based on mastery over the control process. The originality of this study lies in the balance between the conceptual delimitations of the control process, the logical scheme constructed with the attributes that characterize the control process, and the five implications for the training of executive secretarial professionals.